Antibacterial masterbatch and preparation method thereof
By using epoxy modified T i3C2Tx material and thiamine pyrophosphate reaction products as composite antibacterial agents, combined with polypropylene and other materials, antibacterial masterbatches are prepared, which solves the problems of poor performance or single function of the existing antibacterial masterbatches, and the preparation of high-performance antibacterial polypropylene composite materials is achieved.
Patent Information
- Application Number
- CN202411408646.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-10
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-10-10
AI Technical Summary
The existing antibacterial masterbatch has poor performance or single function, making it difficult to meet the needs of high-performance antibacterial polypropylene products.
The reaction product of epoxy modified T i3C2Tx material and thiamine pyrophosphate is used as a composite antibacterial agent, and the antibacterial masterbatch is prepared by melt blending extrusion.
It has achieved excellent antibacterial properties of polypropylene composite materials, significantly improved its mechanical properties, flame retardant properties and antistatic properties, and expanded its application range.
Smart Images

Figure BDA0005077385010000071 
Figure BDA0005077385010000081
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of plastic masterbatch preparation, and particularly relates to an antibacterial masterbatch and a preparation method thereof. Background Art
[0002] Polypropylene has the advantages of low cost, low density, easy processing, good chemical resistance, and excellent mechanical properties. It is the most commonly used thermoplastic polymer in daily life. In recent years, people's requirements for the antibacterial properties of materials have gradually increased. The hydrophobicity and inertness of the polypropylene surface often lead to bacterial contamination, hindering its potential application in the antibacterial field. The introduction of substances with antibacterial activity to achieve antibacterial effects has received widespread attention in the fields of polymer materials and medical and health care. The preparation of antibacterial polypropylene materials has become a hot topic in the research of antibacterial plastics.
[0003] At present, the commonly used antimicrobial agents mainly include natural antimicrobial agents, organic antimicrobial agents and inorganic antimicrobial agents. Among them, natural antimicrobial agents and organic antimicrobial agents have the problems of poor stability, easy decomposition, easy precipitation, etc., while inorganic antimicrobial agents have the problem of poor dispersibility, resulting in the final prepared masterbatch with poor performance or single function. Therefore, it is necessary to provide a high-efficiency antimicrobial masterbatch for the preparation of high-performance antimicrobial polypropylene products. Summary of the invention
[0004] The object of the present invention is to provide an antibacterial masterbatch and a preparation method thereof, so as to solve the problem that the existing masterbatch has poor performance or single function.
[0005] The purpose of the present invention can be achieved through the following technical solutions:
[0006] An antibacterial masterbatch comprises the following raw materials in parts by weight: 70-90 parts of polypropylene, 18-20 parts of maleic anhydride grafted polypropylene, 15-25 parts of composite antibacterial agent, 3-5 parts of dispersant, 3-6 parts of color powder, 2-3 parts of antioxidant and 1-2 parts of ultraviolet absorber.
[0007] The composite antibacterial agent is epoxy-modified Ti3C2T x Reaction products of materials with thiamine pyrophosphate.
[0008] Further, the composite antibacterial agent is prepared by the following steps:
[0009] The epoxy-modified Ti3C2T x The material was ultrasonically dispersed in anhydrous ethanol, and a solution a consisting of thiamine pyrophosphate and deionized water was added. The reaction was stirred at 60°C for 24 hours, and then centrifuged at 8000 rpm for 10 minutes. The upper liquid was discarded, and the precipitate was washed with anhydrous ethanol and vacuum dried to obtain a composite antibacterial agent.
[0010] T3C2T xThe material belongs to a type of two-dimensional transition metal carbon / nitrogen compound (MXene). Similar to graphene, it can inhibit bacteria through physical and chemical effects. The antibacterial mechanism includes physical capture, physical cutting, oxidative stress and membrane component extraction. However, its particle size is small and difficult to disperse, and its compatibility with the polypropylene matrix is poor. Based on this, the present invention first uses 3-(2,3-epoxypropoxy)propyltrimethoxysilane to x The material is treated with coupling agent and then x Active epoxy groups were introduced into the surface of the material, and then the reactive characteristics between amino groups and epoxy groups were used to modify Ti3C2T x Thiamine pyrophosphate was grafted onto the surface of the material and modified to form Ti3C2T x The dispersibility of the material in the polypropylene group is significantly improved, allowing it to effectively exert its antibacterial effect, while the thiazole quaternary ammonium salt structure in thiamine pyrophosphate further enhances the antibacterial effect of the masterbatch.
[0011] T3C2T x The material also has good electrical conductivity. Combined with the good moisture absorption of thiazole quaternary ammonium salt, the evenly dispersed composite antibacterial agent forms a good conductive channel on the surface and inside of the material, giving the composite material good antistatic properties. The evenly dispersed composite antibacterial agent can also be a rigid reinforcing particle, which significantly improves the mechanical properties of the composite material.
[0012] In addition, under high temperature conditions, the Ti3C2T x The decomposition product of the material, TiO2, has a good barrier effect, constructs a "maze" in the matrix, and prolongs the diffusion path of the combustible gas. TiO2 also has excellent catalytic activity, which can promote the carbonization of the polymer matrix, and plays a good catalytic carbonization and smoke suppression role. Moreover, the N, P, and S elements in thiamine pyrophosphate and the Si element in 3-(2,3-epoxypropyloxy)propyltrimethoxysilane form an organic flame retardant system, which together promote the good flame retardant properties of polypropylene composite materials.
[0013] Furthermore, epoxy-modified Ti3C2T x The usage ratio of materials, anhydrous ethanol, thiamine pyrophosphate and deionized water is 0.2g:100mL:0.3-0.5g:10-20mL.
[0014] Furthermore, epoxy-modified Ti3C2T x The material is made by the following steps:
[0015] T i3C2T xThe material was ultrasonically dispersed in anhydrous ethanol, and 3-(2,3-epoxypropoxy)propyltrimethoxysilane was added dropwise. After the addition was completed, stirring was continued for 24 hours, and then centrifuged at 8000 rpm for 10 minutes. The upper liquid was discarded, and the precipitate was washed with anhydrous ethanol and vacuum dried to obtain epoxy-modified Ti3C2T x Material.
[0016] Furthermore, T i3C2T x The usage ratio of materials, anhydrous ethanol and 3-(2,3-epoxypropoxy)propyltrimethoxysilane is 0.8g:400mL:4-6mL.
[0017] Furthermore, T i3C2T x The material is made by the following steps:
[0018] Ti3AlC2 powder was added to a hydrochloric acid solution containing LiF, stirred at 60°C for 72 h, then washed with deionized water and centrifuged until the supernatant pH was 7±0.5, and the resulting precipitate was vacuum dried at 60°C for 24 h to obtain Ti3C2T x Material.
[0019] Furthermore, the usage ratio of Ti3AlC2 powder, LiF and hydrochloric acid solution is 1-1.2g:0.5g:12mL, and the concentration of the hydrochloric acid solution is 4.5mol / L.
[0020] Furthermore, the average particle size of the Ti3AlC2 powder is 38 um.
[0021] Furthermore, the dispersant is one or more of polyethylene wax, stearic acid and ethylene stearamide.
[0022] Furthermore, the toner is one of ultramarine toner, cobalt blue toner, cadmium yellow toner and titanium dioxide.
[0023] Furthermore, the antioxidant is one of antioxidant 1010 and antioxidant 1135.
[0024] Furthermore, the ultraviolet absorber is one of ultraviolet absorber UV-P and ultraviolet absorber UV-1130.
[0025] The method for preparing the antibacterial masterbatch comprises the following steps:
[0026] S1. Put polypropylene, maleic anhydride grafted polypropylene, composite antibacterial agent, dispersant, color powder, antioxidant and ultraviolet absorber in a mixer, and mix them at a speed of 300-500 r / min for 30-60 min to obtain a mixture;
[0027] S2. Transfer the mixed material to a twin-screw extruder, melt extrude, and granulate. The screw speed is 200-300r / min. The temperatures of each zone are: 190-200°C in zone 1, 210-220°C in zone 2, 235-245°C in zone 3, 220-230°C in zone 4, and 200-210°C in zone 5 to obtain antibacterial masterbatch.
[0028] Beneficial effects of the present invention:
[0029] The present invention uses epoxy-modified Ti3C2T x The reaction product of the material and thiamine pyrophosphate is a composite antibacterial agent, polypropylene is used as the base material, and the antibacterial masterbatch is obtained by melt blending and extrusion. Due to the versatility and precise dosage ratio of the composite antibacterial agent, the final polypropylene composite material not only has excellent antibacterial properties, but also has significantly improved mechanical properties, flame retardant properties, and antistatic properties, further expanding the application range of polypropylene composite materials. DETAILED DESCRIPTION
[0030] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0031] The Ti3AlC2 powder in this application has a purity of ≥99% and an average particle size of 38 μm and is from Beijing Lianlixin Technology Co., Ltd.
[0032] Preparation Example 1
[0033] A composite antibacterial agent is prepared by the following steps:
[0034] 0.2 kg epoxy-modified Ti3C2T x The material was ultrasonically dispersed in 100 L of anhydrous ethanol, and a solution a consisting of 0.3 kg of thiamine pyrophosphate and 10 L of deionized water was added. The reaction was stirred at 60°C for 24 hours, and then centrifuged at 8000 rpm for 10 minutes. The upper liquid was discarded, the precipitate was washed with anhydrous ethanol and then vacuum dried to obtain a composite antibacterial agent.
[0035] Epoxy modified Ti3C2T x The material is made by the following steps:
[0036] 0.8kg Ti3C2T xThe material was ultrasonically dispersed in 400 L of anhydrous ethanol, and 4 L of 3-(2,3-epoxypropoxy)propyltrimethoxysilane was added dropwise. After the addition was completed, stirring was continued for 24 h, and then centrifuged at 8000 rpm for 10 min. The upper liquid was discarded, and the precipitate was washed with anhydrous ethanol and vacuum dried to obtain epoxy-modified Ti3C2T x Material.
[0037] T3C2T x The material is made by the following steps:
[0038] 1 kg of Ti3AlC2 powder was added to 12 mL of 4.5 mol / L hydrochloric acid solution containing 0.5 kg of LiF, stirred at 60 °C for 72 h, then washed with deionized water and centrifuged until the supernatant pH was 7 ± 0.5, and the resulting precipitate was vacuum dried at 60 °C for 24 h to obtain Ti3C2T x Material.
[0039] Preparation Example 2
[0040] A composite antibacterial agent is prepared by the following steps:
[0041] 0.2 kg epoxy-modified Ti3C2T x The material was ultrasonically dispersed in 100 L of anhydrous ethanol, and a solution a consisting of 0.5 kg of thiamine pyrophosphate and 20 L of deionized water was added. The reaction was stirred at 60°C for 24 hours, and then centrifuged at 8000 rpm for 10 minutes. The upper liquid was discarded, the precipitate was washed with anhydrous ethanol and then vacuum dried to obtain a composite antibacterial agent.
[0042] Epoxy modified Ti3C2T x The material is made by the following steps:
[0043] 0.8kg Ti3C2T x The material was ultrasonically dispersed in 400 L of anhydrous ethanol, and 6 L of 3-(2,3-epoxypropoxy)propyltrimethoxysilane was added dropwise. After the addition was completed, stirring was continued for 24 h, and then centrifuged at 8000 rpm for 10 min. The upper liquid was discarded, and the precipitate was washed with anhydrous ethanol and vacuum dried to obtain epoxy-modified Ti3C2T x Material.
[0044] T3C2T x The material is made by the following steps:
[0045] 1.2 kg of Ti3AlC2 powder was added to 12 mL of 4.5 mol / L hydrochloric acid solution containing 0.5 kg of LiF, stirred at 60 °C for 72 h, then washed with deionized water and centrifuged until the supernatant pH was 7 ± 0.5, and the resulting precipitate was vacuum dried at 60 °C for 24 h to obtain Ti3C2T x Material.
[0046] Comparative Preparation Example 1
[0047] A composite antibacterial agent is prepared by the following steps:
[0048] 0.8kg Ti3C2T x The material was ultrasonically dispersed in 400 L of anhydrous ethanol, and 4 L of 3-(2,3-epoxypropoxy)propyltrimethoxysilane was added dropwise. After the addition was completed, stirring was continued for 24 h, and then centrifuged at 8000 rpm for 10 min. The upper liquid was discarded, and the precipitate was washed with anhydrous ethanol and vacuum dried to obtain epoxy-modified Ti3C2T x Material, Ti3C2T x The material preparation process is the same as in Example 1.
[0049] Example 1
[0050] An antibacterial masterbatch comprises the following raw materials in parts by weight: 70 parts of polypropylene, 18 parts of maleic anhydride grafted polypropylene, 15 parts of the composite antibacterial agent of Preparation Example 1, 3 parts of ethylene stearamide, 3 parts of cadmium yellow powder, 2 parts of antioxidant 1135, and 1 part of ultraviolet absorber UV-P.
[0051] The method for preparing the antibacterial masterbatch comprises the following steps:
[0052] S1. Put polypropylene, maleic anhydride grafted polypropylene, composite antibacterial agent, dispersant, toner, antioxidant and ultraviolet absorber in a mixer, and mix them at a speed of 300 r / min for 30 min to obtain a mixture;
[0053] S2. The mixed material is transferred to a twin-screw extruder for melt extrusion and granulation. The screw speed is 200 r / min. The temperatures of each zone are: 190° C. for zone 1, 210° C. for zone 2, 235° C. for zone 3, 220° C. for zone 4 and 200° C. for zone 5 to obtain antibacterial masterbatch.
[0054] Example 2
[0055] An antibacterial masterbatch comprises the following raw materials in parts by weight: 80 parts of polypropylene, 19 parts of maleic anhydride grafted polypropylene, 20 parts of the composite antibacterial agent of Preparation Example 2, 4 parts of polyethylene wax, 4 parts of ultramarine color powder, 2.5 parts of antioxidant 1010, and 1.5 parts of ultraviolet absorber UV-P.
[0056] The preparation method of the above antibacterial masterbatch is the same as that of Example 1.
[0057] Example 3
[0058] An antibacterial masterbatch comprises the following raw materials in parts by weight: 90 parts of polypropylene, 20 parts of maleic anhydride grafted polypropylene, 25 parts of the composite antibacterial agent of Preparation Example 2, 5 parts of stearic acid, 6 parts of cobalt blue powder, 3 parts of antioxidant 1135, and 2 parts of ultraviolet absorber UV-1130.
[0059] The preparation method of the above antibacterial masterbatch is the same as that of Example 1.
[0060] Comparative Example 1
[0061] An antibacterial masterbatch is disclosed. Compared with Example 1, the composite antibacterial agent in Example 1 is replaced with the product prepared in Control Preparation Example 1, and the remaining raw materials and preparation process are the same as in Example 1.
[0062] Comparative Example 2
[0063] An antibacterial masterbatch, compared with Example 1, the amount of the composite antibacterial agent in Example 1 is changed from 15 parts to 14 parts, and the other raw materials and preparation process are the same as Example 1.
[0064] Comparative Example 3
[0065] An antibacterial masterbatch, compared with Example 3, the amount of the composite antibacterial agent in Example 3 is changed from 25 parts to 26 parts, and the other raw materials and preparation process are the same as Example 1.
[0066] The masterbatch and polypropylene resin prepared in Example 1 to Example 3 and Comparative Example 1 to Comparative Example 3 were added to the melt hopper of a twin-screw extruder in a mass ratio of 1:3, extruded into granules, and injection molded. The extrusion temperature was 195°C in zone 1, 205°C in zone 2, and 200°C in zone 3 (die head). The main engine speed was 50r / min, the feed speed was 50r / min, and during the injection process, the template zone was 40°C and the injection zone was 200°C. The test specimens were obtained, and then the performance test was performed:
[0067] The tensile strength was tested using the GB / T1014.1-2018 method;
[0068] The impact strength was tested using the GB / T1843-2008 method;
[0069] The antibacterial rate was tested using the GB / T31402-2015 method;
[0070] Refer to the UL-94 flame retardant grade standard to conduct vertical combustion test on the samples to test the flame retardant performance;
[0071] The surface resistance of the composite material strip was measured using a high resistance meter, and the surface resistivity was calculated using the formula Ps = RsL / d, where Ps is the surface resistivity, Rs is the surface resistance, L is the circumference of the parallel electrode (guard electrode), cm, and d is the distance between the two electrodes, cm;
[0072] The results are shown in Table 1:
[0073] Table 1
[0074]
[0075]
[0076] It can be seen from the data recorded in Table 1 that the polypropylene materials obtained in Examples 1-3 have good antibacterial properties, mechanical properties, flame retardancy and antistatic properties.
[0077] Specifically, it can be seen from the test results in Example 1 and Comparative Example 1 that the absence of thiamine pyrophosphate will cause significant deterioration of the antibacterial property, flame retardant property and antistatic property of the composite material.
[0078] Specifically, it can be seen from the test results of Example 1, Comparative Example 2 and Example 3 and Comparative Example 3 that adding too little or too much composite antibacterial agent is not conducive to obtaining a high-performance polypropylene composite material.
[0079] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.
[0080] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. An antibacterial masterbatch, characterized in that: The invention comprises the following raw materials in parts by weight: 70-90 parts of polypropylene, 18-20 parts of maleic anhydride grafted polypropylene, 15-25 parts of composite antibacterial agent, 3-5 parts of dispersant, 3-6 parts of color powder, 2-3 parts of antioxidant, and 1-2 parts of ultraviolet absorber; The composite antibacterial agent is epoxy-modified Ti3C2T x Reaction products of materials with thiamine pyrophosphate; The composite antimicrobial agent is prepared by the following steps: Epoxy-modified Ti3C2T x The material was ultrasonically dispersed in anhydrous ethanol, and a solution a consisting of thiamine pyrophosphate and deionized water was added, stirred and reacted at 60°C for 24 hours, centrifuged, washed and dried to obtain a composite antibacterial agent; Epoxy modified Ti3C2T x The usage ratio of materials, anhydrous ethanol, thiamine pyrophosphate and deionized water is 0.2g:100mL:0.3-0.5g:10-20mL.
2. The antibacterial masterbatch according to claim 1, characterized in that: Epoxy modified Ti3C2T x The material is made by the following steps: Ti3C2T x The material was ultrasonically dispersed in anhydrous ethanol, and 3-(2,3-epoxypropoxy)propyltrimethoxysilane was added dropwise. After the addition was completed, stirring was continued for 24 hours, centrifuged, and the precipitate was washed and dried to obtain epoxy-modified Ti3C2T x Material.
3. The antibacterial masterbatch according to claim 2, characterized in that: Ti3C2T x The usage ratio of materials, anhydrous ethanol and 3-(2,3-epoxypropoxy)propyltrimethoxysilane is 0.8g:400mL:4-6mL.
4. The antibacterial masterbatch according to claim 2, characterized in that: Ti3C2T x The material is made by the following steps: Ti3AlC2 powder was added to a hydrochloric acid solution containing LiF, stirred at 60°C for 72 h, washed with deionized water and centrifuged until the supernatant pH was 7±0.5, and the resulting precipitate was vacuum dried at 60°C for 24 h to obtain Ti3C2T x Material.
5. The antibacterial masterbatch according to claim 4, characterized in that: The dosage ratio of Ti3AlC2 powder, LiF and hydrochloric acid solution is 1-1.2g:0.5g:12mL, and the concentration of hydrochloric acid solution is 4.5mol / L.
6. The antibacterial masterbatch according to claim 4, characterized in that: The average particle size of Ti3AlC2 powder is 38um.
7. A method for preparing the antibacterial masterbatch according to any one of claims 1 to 6, characterized in that: The following steps are involved: S1. Put polypropylene, maleic anhydride grafted polypropylene, composite antibacterial agent, dispersant, toner, antioxidant and ultraviolet absorber in a mixer, and mix for 30-60 minutes to obtain a mixture; S2, melt-extrude and granulate the mixed material to obtain antibacterial masterbatch.
8. The method for preparing an antibacterial masterbatch according to claim 7, characterized in that: During the extrusion granulation process: the screw speed is 200-300r / min, and the temperatures of each zone are: zone 1 190-200℃, zone 2 210-220℃, zone 3 235-245℃, zone 4 220-230℃, zone 5 200-210℃.
Citation Information
Patent Citations
Preparation method of MnO<2> / Ti<3>C<2>T<x>Mxene flexible supercapacitor electrode material
CN108807003A
Preparation method for two-dimensional layered Ti2CTx flexible paper
CN108922793A